VALUES IN CONTEMPORARY INTERNATIONAL BUSINESS - Goxe, François; Nivoix, Sophie; Viegas-Pires, Michaël (ROUTLEDGE, 2025)
To fill the gaps in theoretical and empirical aspects of the existing international business and management literature, this book addresses several major issues of values in international business in a permanently changing world. The current environmental and geopolitical everchanging volatility imposes requirements for continuous revisiting and adaptation of firm international strategies and respective evolution of associated values. This book analyzes these challenges in three core aspects, namely, value changes and developments in a crisis period, emergence of new ways to value creation, and valuerelated intercultural challenges of international business in a volatile wordencompassing context. This book aims to provide a comprehensive analysis of the theoretical and practical aspects related to values in international business, including changes in the value creation process and the adaptation and evolution of firms in an environment affected by various crises. In doing so it sets the goal to assist managers and scholars in better understanding the new challenges in various aspects of international management concerning dynamics in the understanding of values in international business. To address these issues, this book covers topics that have been dedicated insufficient attention in international business and management literature.